Global Disparities in Paediatric Brain Tumour Surgery - Javeria Javed; Fareeha Nisar; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2026)
Paediatric brain tumours are the leading cause of cancerrelated mortality in children worldwide, yet outcomes differ markedly across regions. These differences reflect variation in health system capacity rather than tumour biology alone. This review examines global disparities in paediatric brain tumour surgery, with a focus on how limitations in diagnosis, surgical expertise, and perioperative care shape outcomes in low- and middle-income countries. In resource-limited settings, delays in diagnosis and restricted access to neuroimaging often result in children presenting with advanced disease, larger tumours, and associated hydrocephalus. These factors increase operative risk and limit the likelihood of safe and complete resection. Surgical outcomes are further influenced by constraints in perioperative care, including limited paediatric anaesthesia, intensive care support, and specialized nursing. Gaps in multidisciplinary coordination and restricted access to adjuvant therapies further compromise treatment completion. Long-term follow-up and survivorship care remain inconsistent in many settings, contributing to unrecognized recurrence and avoidable long-term morbidity. Addressing these disparities requires a shift from short-term solutions toward sustained health system strengthening. Priority areas include workforce development, regional surgical capacity, reliable diagnostic and pathology services, and robust cancer registries to support continuity of care and improve survival for children with brain tumours. Keywords: Paediatric neurosurgery, Brain Tumour, Healthcare Disparities, Global health, Lower middleincome countries.